PENGARUH DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PD. BUMI WIRALODRA INDRAMAYU - Meddy Nurpratama (Jurnal Investasi, 2019)
Human resources are a very important part for every company to achieve the goals to be achieved. Company goals can be achieved through high employee performance. The management of the company must be able to increase employee performance by paying attention to factors such as discipline and compensation. Results of research on company performance, PD. Bumi Wiralodra Indramayu in the 2013-2018 period experienced a decline in performance. This study aims to determine the effect of: work discipline on employee performance; compensation for employee performance; and the influence of work discipline and compensation together on employee performance in PD. Bumi Wiralodra Indramayu. The method used in this study is associative, which aims to determine the relationship between two or more variables. Data collection techniques by means of field research, literature study, data analysis and a population of 30 people and the determination of the sample using total sampling. The data analysis follows descriptive analysis, normality test, multicollinearity and multiple regression analysis. The results showed that work discipline had a significant effect on employee performance with a significance value of 0.000 <0.05; compensation has a significant effect on employee performance with a significance value of 0.006 <0.05. Work discipline and compensation together have a significant influence on employee performance in PD. Bumi Wiralodra Indramayu, a significance value of 0.000 <0.05 while the influence of work discipline and compensation on employee performance is 91.9%. The remaining 8.1% is influenced by other factors. Employee performance can be increased if discipline and compensation are considered by the company management. The enactment of regulations that are accompanied by appropriate sanctions will encourage high work discipline and the management of the company to try to meet the needs of employees through appropriate compensation